Investigating Perception to Production Transfer in Children With Cochlear Implants: A High Variability Phonetic Training Study. - Hao Zhang; Xuequn Dai; Wen Ma; Hongwei Ding; Yang Zhang (Journal of Speech, Language & Hearing Research, 2024)
Purpose: This study builds upon an established effective training method to investigate the advantages of high variability phonetic identification training for enhancing lexical tone perception and production in Mandarin-speaking pediatric cochlear implant (CI) recipients, who typically face ongoing challenges in these areas. Method: Thirty-two Mandarin-speaking children with CIs were quasirandomly assigned into the training group (TG) and the control group (CG). The 16 TG participants received five sessions of high variability phonetic training (HVPT) within a period of 3 weeks. The CG participants did not receive the training. Perception and production of Mandarin tones were administered before (pretest) and immediately after (posttest) the completion of HVPT via lexical tone recognition task and picture naming task. Both groups participated in the identical pretest and posttest with the same time frame between the two test sessions. Results: TG showed significant improvement from pretest to posttest in identifying Mandarin tones for both trained and untrained speech stimuli. Moreover, perceptual learning of HVPT significantly facilitated trainees’ production of T1 and T2 as rated by a cohort of 10 Mandarin-speaking adults with normal hearing, which was corroborated by acoustic analyses revealing improved fundamental frequency (F0) median for T1 and T2 production and enlarged F0 movement for T2 production. In contrast, TG children’s production of T3 and T4 showed nonsignificant changes across two test sessions. Meanwhile, CG did not exhibit significant changes in either perception or production. Conclusions: The results suggest a limited and inconsistent transfer of perceptual learning to lexical tone production in children with CIs, which challenges the notion of a robust transfer and highlights the complexity of the interaction between perceptual training and production outcomes. Further research on individual differences with a longitudinal design is needed to optimize the training protocol or tailor interventions to better meet the diverse needs of learners.